2016
DOI: 10.1016/j.resp.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the calculation of D M,CO and V C via the single breath single oxygen tension DL CO/NO method

Abstract: Alveolar-capillary membrane conductance (DM,CO) and pulmonary-capillary blood volume (VC) are calculated via lung diffusing capacity for carbon monoxide (DLCO) and nitric oxide (DLNO) using the single breath, single oxygen tension (single-FiO2) method. However, two calculation parameters, the reaction rate of carbon monoxide with blood (θCO) and the DM,NO/DM,CO ratio (α-ratio), are controversial. This study systematically determined optimal θCO and α-ratio values to be used in the single-FiO2 method that yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
3
14
1
Order By: Relevance
“…However, as can be seen in Table 2, the single breath method tends to yield higher DLNO/DLCO ratios than that of the rebreathe method (presently, mean 5.39 ± 0.43 for single breath vs. 3.58 ± 0.59 for rebreathe), such that approaching the asymptote is not usually an issue. The observation that DLNO/DLCO is slightly higher using the single breath method is found in our laboratory and others (Ceridon et al, 2010; Ceridon et al, 2011; Coffman et al, 2016; Zavorsky and Lands, 2005; Zavorsky and Murias, 2006). …”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…However, as can be seen in Table 2, the single breath method tends to yield higher DLNO/DLCO ratios than that of the rebreathe method (presently, mean 5.39 ± 0.43 for single breath vs. 3.58 ± 0.59 for rebreathe), such that approaching the asymptote is not usually an issue. The observation that DLNO/DLCO is slightly higher using the single breath method is found in our laboratory and others (Ceridon et al, 2010; Ceridon et al, 2011; Coffman et al, 2016; Zavorsky and Lands, 2005; Zavorsky and Murias, 2006). …”
Section: Discussionsupporting
confidence: 83%
“…From both of these studies, our laboratory has concluded that the θ CO equation described by Reeves and Park is ideal, while the optimal α value is dependent on the technique used; ~2.26 for rebreathe and ~4.40 for single breath. This difference can be understood by recognizing that the single breath method, in our laboratory and others, often yields DLNO values somewhat higher than the rebreathe method (Ceridon et al, 2010; Ceridon et al, 2011; Coffman et al, 2016; Snyder et al, 2007; Zavorsky et al, 2014; Zavorsky and Murias, 2006; Zavorsky et al, 2004). Of note, while this inconsistency in DLNO values between the two methods in not completely understood, it is not the focus of this manuscript.…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations